CIAT Soil Carbon Sequestration Research - Sommer, Rolf; Silva, Mayesse Aparecida da; Söderström, Mats; Piikki, Kristin; Mukalama, John; Mutua, John Y.; Kihara, Job Maguta; Tamene, Lulseged D.; Desta, Evan; Verchot, Louis V. (2017)
CIAT Soil Carbon Sequestration Research by Rolf Sommer, CGIAR Research Program on Water, Land and Ecosystems. Presentation made at Soil Carbon Sequestration: Supporting NDCs and donor action. A CGIAR-wide workshop held 12 Nov 2017 at ZEF Center for Development Research, University of Bonn. Workshop organized jointly by: CGIAR Research Programs on Climate Change, Agriculture and Food Security (CCAFS); Water, Land and Ecosystems (WLE) and Forests, Trees and Agroforestry (FTA).